2015
DOI: 10.1590/2359-3997000000029
|View full text |Cite
|
Sign up to set email alerts
|

Translational research into gut microbiota: new horizons on obesity treatment: updated 2014

Abstract: Obesity is currently a pandemic of worldwide proportions affecting millions of people. Recent stu dies have proposed the hypothesis that mechanisms not directly related to the human genome could be involved in the genesis of obesity, due to the fact that, when a population undergoes the same nutritional stress, not all individuals present weight gain related to the diet or become hyperglycemic. The human intestine is colonized by millions of bacteria which form the intestinal flora, known as gut flora. Studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 63 publications
0
21
0
2
Order By: Relevance
“…The present experiment attempted to evaluate the short and long-term influence of two kinds of nutritional deficiencies on the bacterial community associated with intestinal mucosa in sea bass individuals. When animals are subjected to nutritional stress, not all individuals may react in a similar way, partly depending on intestinal microbiota [19]. A common garden approach was used to test the effects of possible social interaction and inter-individual contamination.…”
Section: Discussionmentioning
confidence: 99%
“…The present experiment attempted to evaluate the short and long-term influence of two kinds of nutritional deficiencies on the bacterial community associated with intestinal mucosa in sea bass individuals. When animals are subjected to nutritional stress, not all individuals may react in a similar way, partly depending on intestinal microbiota [19]. A common garden approach was used to test the effects of possible social interaction and inter-individual contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, elevated release of LPS and/or increased FFAs levels led to elevated production of pro-inflammatory cytokines [i.e., interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α] in the gut ( 13 17 ). The second step may consist in increased delivery of intestinal LPS, pro-inflammatory cytokines, and FFAs into the systemic circulation and portal circulation, thus leading to a systemic low-grade inflammation ( 15 , 18 ). Elevated plasma FFAs and LPS can upregulate the expression of TLRs in circulating macrophages, enabling macrophages to be activated (M1 phenotype), which in turn produce proinflammmatory cytokines ( 11 , 12 ).…”
Section: Hfds Induce a Systemic Chronic Low-grade Inflammationmentioning
confidence: 99%
“…Once LPS is released systemically, monocytes and phagocytic cells produce large amounts of cytokines such as tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and IL-8 23. Conditions associated with abnormal intestinal permeability may increase LPS absorption and induce a state of metabolic endotoxemia characterized by elevated serum LPS concentration 45. The origin of metabolic endotoxemia is still unclear, but it is strongly suggested that it may be associated with changes in the gut microbiota, especially in diets with high fat content, leading to increased activation of inflammatory pathways and impaired insulin signaling 1…”
Section: Introductionmentioning
confidence: 99%
“…It has also been speculated that LPS may be related to the etiology of inflammation in CD. With increased bowel permeability, gut bacterial overgrowth occurs in IBD 45. The combination of abnormal microbiota and a damaged mucosal barrier may increase serum LPS levels 7…”
Section: Introductionmentioning
confidence: 99%